2007
DOI: 10.1063/1.2712439
|View full text |Cite
|
Sign up to set email alerts
|

Absolute line intensities for formic acid and dissociation constant of the dimer

Abstract: Absolute line intensities in the nu(6) and nu(8) interacting bands of trans-HCOOH, observed near 1105.4 and 1033.5 cm(-1), respectively, and the dissociation constant of the formic acid dimer (HCOOH)(2) have been measured using Fourier transform spectroscopy at a resolution of 0.002 cm(-1). Eleven spectra of formic acid, at 296.0(5) K and pressures ranging from 14.28(25) to 314.0(24) Pa, have been recorded between 600 and 1900 cm(-1) with an absorption path length of 19.7(2) cm. 437 integrated absorption coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
5
36
0
Order By: Relevance
“…[267]. Recently, Vander Auwera et al [262] reported absolute line intensities measurements for the ν 6 and ν 8 bands using…”
Section: Hcooh (Molecule 32)mentioning
confidence: 99%
See 1 more Smart Citation
“…[267]. Recently, Vander Auwera et al [262] reported absolute line intensities measurements for the ν 6 and ν 8 bands using…”
Section: Hcooh (Molecule 32)mentioning
confidence: 99%
“…This edition of HITRAN constitutes a major update of the information provided for formic acid: the 9-μm region has been completely replaced [262,263], and there is the first inclusion of the 5.6-μm region [264]. These regions correspond to the strong ν 6 and ν 3 bands, respectively.…”
Section: Hcooh (Molecule 32)mentioning
confidence: 99%
“…These equilibrium constants fall in two broad categories -vapor density measurements 27 and spectroscopic monomer determinations. 26 The average value for K p p • from the vapor density results (including photoacoustic resonance, 28 but excluding the data which need major temperature extrapolation) is about 265(20) Pa, whereas spectroscopy yields significantly higher values above 350 Pa. Combining the two types of data set with a double weight for the single reliable spectroscopic source, one arrives at 300(50) Pa. Having narrowed down the partition function uncertainty in the present work to less than 10%, this K p discrepancy is now determining the accuracy of the resulting dissociation energy of formic acid dimer.…”
Section: Dissociation Energymentioning
confidence: 99%
“…Thus, the mixing ratio of organic vapor (partial pressure of order 1 × 10 −3 Pa or less) in an atmosphere of ∼ 80 × 10 3 Pa continuously flowing organic-free N 2 would be of order 1 × 10 −8 or lower. Assuming that di-and mono-carboxylic acids have similar dimerization properties (the dissociation constants for monocarboxylic acids in the gas phase are large, e.g., formic acid, 3.6 × 10 2 Pa at 296 K, Vander Auwera et al, 2007), that the effect of chain length on enthalpy of dimerization is minimal (cf., Eq. 7 of Tsonopoulos and Prausnitz, 1970) and solving the quadratic equation as described in, e.g., Zuend et al (2011), the fraction of molecules dimerized would be ∼ 1 per 1 × 10 8 for a sample with p •,L (T ) ∼ 1 × 10 −6 Pa.…”
Section: C2 Dimerization Of Gas-phase Organicsmentioning
confidence: 99%